TECTONIC SETTING OF THE VARDAR SUTURE ZONE (DINARIC-HELLENIC BELT): THE EXAMPLE OF THE KOPAONIK AREA (SOUTHERN SERBIA) - Zelic, Mario; Marroni, Michele; Pandolfi, Luca; Trivić, Branislav (Ofioliti, 2010)
In the tectonic setting of the Dinaric-Hellenic belt, the Vardar Zone is represented by a NW-SE to N-S striking assemblage of oceanic and continental units, each showing different metamorphic grade and deformation features. In this paper, a detailed description of the stratigraphic and structural features of the tectonic units cropping out in the Kopaonik area, belonging to the Vardar Zone of Serbia, is presented. In addition, a 1:50.000 scale geological map of the studied area is also provided. In the Kopaonik area is present a stack of tectonic units, originated during the Alpine deformation phases and referred to both External and Central Vardar Zones of Dimitrijevic´ (1997). These units are represented, from bottom to top, by the Kopaonik Metamorphic Complex, the Brzec´e Unit, the Subophiolite Mélange, the Ophiolite Unit and the Brus Unit. The stack of tectonic units is intruded by Early Oligocene granitoids, referred to as the Kopaonik Intrusive Complex. Moreover, the relationships among the tectonic units are unconformably covered by Miocene volcanic rocks and sedimentary deposits. The stratigraphic and structural dataset presented in this paper allows some considerations about the paleogeographic domain of origin for the successions of the different units as well as some interpretations about the tectonic history of the Vardar Zone.